Electrical characterization of Al/MEH-PPV/p-Si Schottky diode by current-voltage and capacitance-voltage methods - Aydin, Mehmet Enver; Yakuphanoğlu, Fahrettin; Eom, Jae-Hoon; Hwang, Do-Hoon (Elsevier, 2007)
The electrical characterization of the Al/poly[2-methoxy-5-(2'-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV)/p-Si structure has been investigated by current voltage and capacitance-voltage methods. The Al/MEH-PPV/p-Si Schottky diode with the ideality factor value of 1.88 obeys a metal-interfacial layer-semiconductor (MIS) configuration rather than an ideal Schottky diode due to the existence of an insulating layer on the organic semiconductor. The barrier height (Phi(b,o) = 0.80 eV) obtained from the I-V characteristic is lower than the barrier height (Phi(b,o) = 1.19eV) obtained from the C-V characteristic. The discrepancy between Phi(b,o)(I-V) and Phi(b,0)(I-V) can be due to the existence of the interfacial native oxide and the organic MEH-PPV layers between the semiconductor and Schottky contact metal. The barrier height value for the Al/MEH-PPV film/p-Si/Al contact obtained at the room temperature that is significantly larger than that for the conventional Al/p-Si Schottky diode. The density distribution curves of the interface states is in the range (0.32-E-v) to (0.68-E-v)eV. The interface state density N-ss ranges from 3.84 x 10(14) cm(-2) eV(-1) in (0.32-E-v)eV to 1 x 10(14) cm(-2) eV(-1) in (0.68-E-v)eV, of the Al/MEH-PPV/p-Si. The interface state density has an exponential rise with bias from the midgap towards the top of the valence band of the p-Si. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: organic and inorganic semiconductor contact and Schottky barrier height; ideality factor; series resistance; interface states distribution